Phosphorus in minerals from granitic rocks and quartz veins from Segura, central Portugal - Antunes, I.M.H.R. (2011)
At Segura there are different minerals containing phosphorus in their compositions. K-feldspar of granitic rocks has higher P2O5 than coexisting plagioclase. K-feldspar and ablite of Li-bearing granitic pegmatite veins have higher P2O5 content than those of respective feldspar fro two-mica granite, probably due to fractional crystallization of the granite magma. Feldspars from muscovite granite and aplite veins have the highest P2O5 content and these rocks are related. Hydroxiapatite occurs in granitic rocks and quartz veins. Fluorapatite also occurs in two-mica granite and muscovite granite. Coexisting montebrasite and natromontebrasite were found in Li-bearing pegamtite veins. Gormanite occurs in the muscovite granite. Mimetite with unusual As/P ratio of 1.04 and kintoreite are alteration products of galena in quartz veins.